The Relationship Between Adhocracy Culture and Innovative Work Behavior: The Role of Job Satisfaction as a Mediator - Eikla Luwlu Yasmina; Arum Etikariena (JURNAL PSIKOLOGI, 2022)
Organizational culture is proven to have an influence on the work behavior of employees. This study aims to reveal the relationship between adhocracy as an organizational culture and employee innovative behavior, mediated by job satisfaction. There are 110 employees as respondents in this study who come from several start-up companies from various industries. Convenience sampling is used as the sampling method in this study. Mediation analysis using Hayes' PROCESS Macro (Model 4) was performed in this study. The results of data analysis showed that job satisfaction partially mediates the relationship between the organizational culture of adhocracy and innovative work behavior. The implications of this study can be considered by organizations to improve and increase their supports for innovation and supports for their employees’ job satisfaction, with the purpose of the employees’ innovative work behaviors will emerge and eventually that behavior will give benefits for the organization.Keywords: adhocracy culture, innovative work behavior, job satisfaction, mediation analysis, start-up company